2008
DOI: 10.1039/b806900j
|View full text |Cite
|
Sign up to set email alerts
|

[Cyanil]22− dimers possess long, two-electron ten-center (2e−/10c) multicenter bonding

Abstract: A long, two-electron ten-center (2e(-)/10c) [8 carbon plus 2 oxygen] bond in diamagnetic dimers of radical-anion tetracyano-1,4-benzoquinoneide (cyanil, [Q] (-)), [Q](2)(2-), is described by B3LYP and CASSCF(2,2)/MCQDPT calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 32 publications
1
40
0
Order By: Relevance
“…Theoretical studies indicated that all [TCNE] 2 2À dimers exhibit long, 2e À /4c (c = center) CÀC bonds, and are prototypes for long, multicenter C À C bonds between radical anions. More recently, long, multicenter C À C bonding has also been observed for [cyanil] 2 2À (2e À /10c (8C + 2O)), [11] [TTF] 2 2 + (TTF = tetrathiafulvalene) (2e À /10c (6C + 4S)), [13] di(2,5,8-tri-tert-butylphenalenyl) (2e À /14c (14C)), [14,15] [tetracyanopyrazine] 2 2À (2e À /8c (8C)), [16] [TCNQ] 2 2À (TCNQ = 7,7,8,8-tetracyano-p-quinodimethane, 2e…”
Section: + a C H T U N G T R E N N U N G [Tcne]mentioning
confidence: 91%
See 1 more Smart Citation
“…Theoretical studies indicated that all [TCNE] 2 2À dimers exhibit long, 2e À /4c (c = center) CÀC bonds, and are prototypes for long, multicenter C À C bonds between radical anions. More recently, long, multicenter C À C bonding has also been observed for [cyanil] 2 2À (2e À /10c (8C + 2O)), [11] [TTF] 2 2 + (TTF = tetrathiafulvalene) (2e À /10c (6C + 4S)), [13] di(2,5,8-tri-tert-butylphenalenyl) (2e À /14c (14C)), [14,15] [tetracyanopyrazine] 2 2À (2e À /8c (8C)), [16] [TCNQ] 2 2À (TCNQ = 7,7,8,8-tetracyano-p-quinodimethane, 2e…”
Section: + a C H T U N G T R E N N U N G [Tcne]mentioning
confidence: 91%
“…Additionally, dispersion also adds energetic stability to the [TCNE]C À ···A C H T U N G T R E N N U N G [TCNE]C À interaction. [10][11][12] The interaction between two [TCNE] ·À moieties is thus a long, multicenter C À C bond, because it differs from a conventional covalent bond in the genesis of the energetic stabilization, and longer equilibrium distances. Note that the [TCNE] 2 2À dimers present in [cation + ] 2 A C H T U N G T R E N N U N G [TCNE] 2 2À are diamagnetic, as they have a closed-shell singlet ground state, in good agreement with the experimental observations.…”
Section: + a C H T U N G T R E N N U N G [Tcne]mentioning
confidence: 99%
“…8 Other examples (Chart 2) include anionic species, e.g. 7,7,8,8-tetracyano-p-quinodimethanide ([TCNQ] •− ), 9−11 1,2,4,5-tetracyanobenzene ([TCNB] •− ), 12,13 1,2,4,5-tetracyanopyrazine ([TCNP] •− ); 14 cationic species, e.g., tetrathiafulvalenium ([TTF] + ); 15 and neutral radicals, e.g., substituted phenalenyl.…”
Section: Instructionmentioning
confidence: 97%
“…18 Computational studies have revealed the presence of such bond critical points in several dimers indicating a closed shell singlet ground state configuration. 14,[19][20][21] To the best of our knowledge, however, direct experimental evidence for such (3, −1) bond critical points from X-ray diffraction studies of radical dimers has not been reported.…”
Section: Electronic Structure and Bondingmentioning
confidence: 99%